Book Reviews. Issue 1 (1st March 2019) - Andrews, Naomi J.; Coquard, Benoit
Abstract : Gavin Murray-Miller, The Cult of the Modern: Trans-Mediterranean France and the Construction of French Modernity (Lincoln: University of Nebraska Press, 2017). John Murphy, Yearning to Labor: Youth, Unemployment, and Social Destiny in Urban France (Lincoln: University of Nebraska Press, 2017).